KONTRIBUSI IMAM AL-GHAZALI TERHADAP EKSISTENSI TASAWUF - Asmaran Asmaran (Al-Banjari : Jurnal Ilmiah Ilmu-Ilmu Keislaman, 2020)
In the first and second centuries of the Hijrah before the presence of Imam al-Ghazali, whose teachings of Sufism at that time were moral and practical, in the third and fourth centuries of Hijrah the teachings of Sufism developed towards philosophical understandings such as Ittihad and Hulul which are viewed by some scholars (theologians and fuqaha) have deviated from the teachings of Islam, as a result of which Sufism almost dies. In such a situation, in the fifth century AH, Imam al-Ghazali appeared to save him by trying to integrate between the teachings of Sufism with the teachings of fiqh and kalam, between fact and sharia, as can be seen in his book Ihya '' Ulum al-Din (Reviving the Sciences Religion), so he is often referred to as Hujjatul Islam (Defender of Islam) because of his efforts to harmonize the teachings of Islam in complete unity.